The Greek polis and the invention of democracy: a politico-cultural transformation and its interpretations - Jóhann Páll Árnason; Raaflaub, Kurt A.; Wagner, Peter (Ancient world comparative histories, 2013)
"The Greek Polis and the Invention of Democracy presents a series of essays that trace the Greeks' path to democracy and examine the connection between the Greek polis as a citizen state and democracy as well as the interaction between democracy and various forms of cultural expression from a comparative historical perspective and with special attention to the place of Greek democracy in political thought and debates about democracy throughout the centuries."--Publisher's website